Is Intraoperative Fluoroscopy Necessary to Confirm Device Position for Femoral-Sided Cortical Suspensory Fixation during Anterior Cruciate Ligament Reconstruction? - Balldin, B. Christian; Nuelle, Clayton W.; DeBerardino, Thomas M. (The Journal of Knee Surgery, 2020)
Increased laxity within the graft construct system can lead to graft failure after anterior cruciate ligament (ACL) reconstruction. Suboptimal cortical device positioning could lead to increased laxity within the system, which could influence the mechanics and function of the graft reconstruction. This study evaluates the benefit of intraoperative fluoroscopy to confirm device position on the femur during ACL reconstruction using cortical suspensory fixation. One hundred consecutive patients who underwent soft tissue ACL reconstruction using a suspensory cortical device for femoral fixation were retrospectively evaluated. Patients were split into two groups: Group A utilized anteromedial portal visualization and had intraoperative fluoroscopic imaging performed at the time of ACL graft fixation to confirm femoral device placement on the lateral femoral metaphyseal cortex. Group B utilized anteromedial portal visualization alone. Both groups had radiographic X-rays performed at the first postoperative visit to evaluate device location and all images were independently evaluated by three fellowship trained orthopaedic surgeons. Device position was classified as optimal if there was complete apposition of the entire device against the femoral cortex and suboptimal if it was > 2 mm off the cortex. Fisher's exact test, analysis of variance, and 95% confidence intervals were calculated to compare the groups for statistical significance. The results showed 0/60 (0%) patients in group A had suboptimal device position at postoperative follow-up, while 4/40 (10%) patients in group B had suboptimal device position (p = 0.013). There were no graft failures in group A and one graft failure in group B. There was a significant difference in cortical device position in patients who had intraoperative fluoroscopic imaging versus patients who had no intraoperative imaging. The use of confirmatory intraoperative imaging may be beneficial to confirm appropriate device location when using a femoral cortical suspensory fixation technique for ACL reconstruction.
Keywords: ACL reconstruction; cortical suspensory fixation; intraoperative imaging; anteromedial portal; device position